Diseño y elaboración de material didáctico en kichwa para el aprendizaje de lenguaje y literatura en el sexto año de educación general básica, en la escuela Vasco Núñez de Balboa, de la comunidad el Arba, parroquia La Esperanza, cantón Ibarra. - Pupiales Guatemal, Martha Cumandá (2015)
Nothing can reflect a reality as close as that lived from the personal experience of the researcher. Be part of the indigenous population of the ethnic karanki, a resident of the parish the Hope of the canton Ibarra, facilitated a holistic understanding of the problem related to lack of implementation of inclusive intercultural strategies in the learning process of the subject in Language and Literature with students in seventh grade general education basic educational unit "Vasco Nuñez de Balboa" in the community of the Abra. For the child population is indigenous to say the least, very complicated acquire knowledge in a maternal language. This is what happens traditionally in the public and private schools established in the marginal rural areas with high indigenous population density, with Spanish speaking teachers and with little training in the implementation of inclusive teaching practices. The research considers important to work with intercultural strategies in the development of the learning process, on the basis of the teaching materials, important resources for the achievement of the objectives, because they have the advantage of owning three basic characteristics that facilitate the rapprochement of the student toward the learning contents: the display through images, the perception of the messages, using the sequence of signals and participation, exploration and manipulation, through the actions that must be run to build their own knowledge. If so, joins the use of the native language of students as a strategy for understanding inclusive that addresses their individual characteristics, then, this project will contribute significantly to the achievement of knowledge with good results.